2018
DOI: 10.1136/bmjgh-2018-000716
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalising an evidence-informed approach to guideline development: progress and challenges at the World Health Organization

Abstract: This study explored experiences, perceptions and views among World Health Organization (WHO) staff about the changes, progress and challenges brought by the guideline development reforms initiated in 2007. Thirty-five semistructured interviews were conducted with senior WHO staff. Sixteen of the interviewees had in-depth experience with WHO’s formal guideline development process. Thematic analysis was conducted to identify key themes in the qualitative data, and these were interpreted in the context of the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…The present analysis, divided into status diagnoses (Stages 1 and 2) and decision-making processes (Stage 3) was an attempt to systemize information about the extent of the risks associated with BBI and the essential stages of analysis for the preparation of further stages (i.e., proposed solutions). This is consistent with a methodological “mixed research approach” represented by other researchers in public health and healthcare policy [ 38 , 39 , 40 , 41 , 42 ]. Through its use of qualitative inquiry, the current study aimed to understand the extent to which the identified problems and opinions are common among the group of participating experts.…”
Section: Discussionsupporting
confidence: 88%
“…The present analysis, divided into status diagnoses (Stages 1 and 2) and decision-making processes (Stage 3) was an attempt to systemize information about the extent of the risks associated with BBI and the essential stages of analysis for the preparation of further stages (i.e., proposed solutions). This is consistent with a methodological “mixed research approach” represented by other researchers in public health and healthcare policy [ 38 , 39 , 40 , 41 , 42 ]. Through its use of qualitative inquiry, the current study aimed to understand the extent to which the identified problems and opinions are common among the group of participating experts.…”
Section: Discussionsupporting
confidence: 88%
“…The development of high-quality guidelines is a rigorous and complex process that requires an average of two to three years per guideline [1]. Due to the rapid accumulation of new evidence, guideline development should be followed by revisions and update as necessary [2].…”
Section: Introductionmentioning
confidence: 99%
“…The present analysis, divided into status diagnosis (stages 1 and 2) and decision-making processes (stage3), was an attempt to systemize information about the extent of the risks associated with BBI and the essential stages of analysis for the preparation of further stages (i.e., proposed solutions). This is consistent with a methodological "mixed research approach" represented by other researchers in the field of public health and healthcare policy [36][37][38][39][40]. Rather than employing quantitative methods to measure a phenomenon, the current study aimed to understand the extent to which the identified problems and opinions are common among the group of participating experts.…”
Section: Resultsmentioning
confidence: 66%